THEORETICAL CONTENTIONS ON METAPHOR (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
For most people, metaphor is a literary invention, a rhetorical flourish; it's a matter of extraordinary language, not everyday speech. Furthermore, metaphor is usually seen as a property of language alone—that is, as something that has to do with words rather than ideas or deeds. The majority of people believe they can live happily without metaphor because of this. Conversely, we have discovered that metaphor is widely used in daily life—not just in speech but also in cognition and behavior.